Molecular dissection of interactions between components of the alternative pathway of complement and decay accelerating factor (CD55) - Harris, C; Abbott, R; Smith, R; Morgan, B; Lea, S (2005)
The complement regulatory protein decay accelerating factor (DAF; CD55), inhibits the alternative complement pathway by accelerating decay of the convertase enzymes formed by C3b and factor B. We show, using surface plasmon resonance, that in the absence of Mg2+, DAF binds C3b, factor B, and the Bb subunit with low affinity (KD, 14 ± 0.1, 44 ± 10, and 20 ± 7 μM, respectively). In the presence of Mg2+, DAF bound Bb or the von Willebrand factor type A subunit of Bb with higher affinities (KD, 1.3 ± 0.5 and 2.2 ± 0.1 μM, respectively). Interaction with the proenzynie C3bB was investigated by flowing factor B across a C3b-coated surface in the absence of factor D. The dissociation rate was dependent on the time of incubation, suggesting that a time-dependent conformational transition stabilized the C3b-factor B interaction. Activation by factor D (forming C3bBb) increased the complex half-life; however, the enzyme became susceptible to rapid decay by DAF, unlike the proenzyme, which was unaffected. A convertase assembled with cobra venom factor and Bb was decayed by DAF, albeit far less efficiently than C3bBb. DAF did not bind cobra venom factor, implying that Bb decay is accelerated, at least in part, through DAF binding of this subunit. It is likely that DAF binds the complex with higher affinity/avidity, promoting a conformational change in either or both subunits accelerating decay. Such analysis of component and regulator interactions will inform our understanding of inhibitory mechanisms and the ways in which regulatory proteins cooperate to control the complement cascade.